2009
DOI: 10.1111/j.1432-2277.2009.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Low toxicity regimens in renal transplantation: a country subset analysis of the Symphony study

Abstract: Summary Regional transplant practices may affect clinical outcomes within multinational studies. This study evaluated whether the overall results from the Symphony study can be generalized to the participating countries. De novo adult renal transplant recipients (n = 1645) were randomized to receive standard‐dose cyclosporine, or daclizumab induction plus low‐dose cyclosporine, low‐dose tacrolimus, or low‐dose sirolimus, all in addition to mycophenolate mofetil and steroids. Data for the highest patient‐recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Six of the 20 primary studies, in which 1 or more treatment arms used Advagraf or Prograf, measured BMI at baseline, with mean values that varied from 21.8 kg/m 2 to 29.2 kg/m 2 [ 17 , 19 , 24 , 31 , 36 , 80 ]. Based on 2 studies, the percentage of patients with diabetes in individual treatment arms was between 6.9% of 390 patients and 28.3% of 212 patients [ 26 , 37 ]. People of White race (11 studies) accounted for between 65.8% of 243 and 95.8% of 309 patients in individual treatment arms [ 17 , 19 , 24 26 , 28 , 29 , 32 , 35 , 37 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six of the 20 primary studies, in which 1 or more treatment arms used Advagraf or Prograf, measured BMI at baseline, with mean values that varied from 21.8 kg/m 2 to 29.2 kg/m 2 [ 17 , 19 , 24 , 31 , 36 , 80 ]. Based on 2 studies, the percentage of patients with diabetes in individual treatment arms was between 6.9% of 390 patients and 28.3% of 212 patients [ 26 , 37 ]. People of White race (11 studies) accounted for between 65.8% of 243 and 95.8% of 309 patients in individual treatment arms [ 17 , 19 , 24 26 , 28 , 29 , 32 , 35 , 37 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the Transplantation Service of the Hospital Israelita Albert Einstein adopted the strategy of using lower doses of calcineurin inhibitor, aiming at intermediary levels. Another difficulty in comparing the renal function results of each of the groups evaluated here with those of other studies is that only a few of them defined renal function as a primary outcome (23) . Another important outcome evaluated in this study was CMV infection.…”
Section: Discussionmentioning
confidence: 70%
“…The authors believe that optimizing exposure to mycophenolate mofetil through therapeutic drug monitoring can improve the allograft function in patients receiving a cyclosporine-based regimen. A subset analysis of the Symphony study showed that patients from different countries exhibit different renal functions (26). In the Symphony study, less than 2% of the patients were black, whereas in the United States in 2006, more than 35% of patients who were awaiting kidney transplantation were black.…”
Section: Resultsmentioning
confidence: 99%